Optimization of Satbinmas Through Sambang to Reduce the Rate of Motor Vehicle Theft Crimes at Kudus Police - Muhammad Ardiansyah Irianto (Advances in Police Science Research Journal, 2024)
Among several criminal acts that occurred at the Kudus Police, the theft case was one of the highest. As a pre-emptive function, Satbinmas is responsible for reducing the number of criminal cases of theft through prevention activities such as sambang. The implementation of the sambang that has been carried out is considered not to be effective and this encourages the author to research the topic of prevention carried out by Satbinmas to reduce the number of criminal cases of theft so that conducive security and order can be maintained. This study applied a descriptive qualitative approach to field research with data collection techniques in the form of interviews, observations, and also documentation studies. To validate the data obtained, a triangulation process was carried out and analyzed by reduction measures, data presentation, and conclusion. The findings found in the field are analyzed using sambang theory, management theory, organizational resource theory and crime prevention theory, and Perpol number 1 of 2021 concerning community policing. Broadly speaking, the problem encountered in the field is that there is no SOP to guide members in carrying out sambang activities to prevent motorized vehicle theft, Satbinmas resources are still experiencing a shortage of personnel as specified in the list of personnel composition in Perpol Number 21 of 2021 concerning relationship procedures. Work. The suggestions proposed by the author are the formulation of SOPs that can be guided by members, determining work priority scales, empowering communities by implementing community policing, strengthening cross-sectoral.